Developing a buried herbicide method to assess rooting depth of different rice cultivars ( Oryza sativa L.): Developing a buried herbicide method to assess rooting depth of different rice cultivars ( Oryza sativa L.) - F, zainab; Price, A. H.; Robinson, D. (Journal of Kerbala for Agricultural Sciences, 2018)
Rice (Oryza sativa L.) is one of the main staple foods of the world. With the increase of population and the deficit of irrigated water, the increase in rice production that is predicted will be dependent on areas prone to drought. Root depth is important for plant growth and survival during drought because of its role in facilitating water uptake from deep soil layers. By advances in genomics, the plant root systems can be linked to quantitative trait locus (QTL) information to achieve a most beneficial design of root system architecture. There is a demand to develop and validate techniques that permit estimation of the root system. Therefore, one technique (a buried TRIK and Diuron herbicide method at depth 30 cm) was used in this study to assess root traits in a total of 32 rice cultivars. The results from these screens was assessed with root traits measured on the same cultivars in the rhizotrons, hydroponic and non-woven fabric experiments. Correlations between these methods showed that herbicide score at day 35 was most strongly related to traits of the rhizotron experiment, especially number of roots passed 50 cm at 35 days, root angle at day 21, root thickness, water use and % root mass. Using all of these traits obtained in the rhizotron in a best subset regression suggests that up to 71% of the variation in herbicide score can be explained. These data strongly imply that symptoms are related to root development and transpiration demand and are therefore ideal for assessing water extraction by roots at depth. Therefore, developing a cost effective high-throughput system that can measure traits related to drought avoidance on a large number of plants would aid genetic studies in breeding.